A chitosan/fucoidan nanoparticle-loaded pullulan microneedle patch for differential drug release to promote wound healing. (15th April 2023) - Younas, Ayesha; Dong, Zhuolin; Hou, Ziye; Asad, Muhammad; Li, Mengru; Zhang, Nan
Abstract: Wound healing is a largely unmet medical issue in trauma, burn, and diabetes. In this study, a pullulan-based and nanoparticle-loaded smart microneedle patch is designed to release drugs differentially based on the needs of wound healing. Chitosan and fucoidan are first used to prepare moxifloxacin (MOX)-loaded nanoparticles (MOXNPs) with a diameter of 258.0 ± 10.86 nm, PDI 0.19 ± 0.06, and surface charge 45.1 ± 3.9 mV. MOXNPs, lidocaine (LH), and thrombin (TH) are then incorporated to a 30 % ( w /w) pullulan-based microneedle patch (TH + LH + MOXNPs@MN). TH + LH + MOXNPs@MN possesses uniform and cone-shaped microneedles with a length of 725 μm, demonstrating good biocompatibility, sufficient strength for skin penetration, fast skin dissolution within 55 ± 5 min, rapid release of TH and LH within 1 h, and sustained release of MOX for 24 h. TH + LH + MOXNPs@MN heals mice skin wounds completely within 7 days and restores collagen deposition with accelerated cell proliferation, granulation, and reduced pro-inflammatory cytokines. In conclusion, this study utilizes combined polysaccharides to develop a smart multifunctional microneedle platform that achieves rapid hemostasis/analgesia and sustained bactericidal action. The smart and combined therapy is a potential strategy for high-quality wound healing. Graphical abstract: Unlabelled Image Highlights: Chitosan, fucoidan, and pullulan can be fabricated into an advanced delivery system. A smart nanoparticle-loaded microneedle patch differentially releases therapeutics. Rapid hemostasis/analgesia and sustained bactericidal effect promotes wound healing. Pain management is very beneficial to a combined therapy for wound healing.